Get Shorty. The complete second season [videorecording (DVD)] - Arkin, Adam; Mayer, Daisy von Scherler; O'Dowd, Chris, 1980-; Romano, Ray; Bridgers, Sean; Leonard, Elmore, 1925-2013 (MGM, 2019)
A mobster attempts to leave his criminal background behind and becomes a movie producer.